Desarrollo de un aplicativo móvil multiplataforma para el sector turístico hotelero del cantón la Maná. - Enríquez Pastuña, Franklin Geovanny (2022)
La Maná canton is characterized by welcoming a large number of tourists on festive dates celebrated in the country and the city. The collection of information points out to a mobile application development, which will allow publicizing the reservation services that a single hotel in the city will offer. The research problem is based on the fact that tourists do not know where to reserve a room, they do not specifically identify all the hotels that exist. For this reason, the researchers raised as main objective to develop and implement a mobile application for the tourism and hotel industry specifically in El Refugio D' Grace hotel. The methods used during this study were: bibliographical research which facilitated information about the topic of the mobile application, and the field research which provided information to obtain the requirements through interviews and surveys. For the framework, the Scrum methodology was employed in this way different tasks were established and fully accomplished. Finally, the main development tools were Android Studio for code programming, and the use of a Flutter Framework as part of the application design to operate dynamically when interacting with the users and consequently the information will be stored in the PostgreSQL database. The obtained results showed that the application is suitable for generating a room reservation service at El Refugio D' Grace hotel.